Blended learning and simulation in nursing education: A quasi-experimental study on a nursing institute - Soumia Merrou; Abdelmounaim Baslam; Abdellah Idrissi Jouicha; Zakaria Ouhaz; Ahmed Rhassan El Adib (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: The nursing module teaches basic nursing principles and procedures to undergraduate nursing students. This course is important for the acquisition of procedural and psychomotor skills. The aim of the present study is to evaluate the influence of blended training on the acquisition of practical skills related to gastric insertion tubes.MATERIALS AND METHODS: A quasi-experimental study was undertaken, containing three groups: The blended group benefited from e-learning, followed by simulation), while the two groups benefited from theoretical teaching and procedural simulation. Then, the degrees of acquisition of declarative and procedural knowledge and the time of completion were measured.RESULTS: The declarative knowledge grade was higher in the Simulation (16.07) and Blended (15.21) groups than in the Traditional Group (11.66), with a statistically significant difference (P < 0.001). The results also showed a statistically significant difference between the procedural knowledge grades of the three groups (P < 0.001). A statistically significant correlation was detected between declarative and procedural knowledge scores (r = 0.58, P < 0.001) and a negative correlation between procedural knowledge and the time of completion (r = -0.422, P < 0.001).CONCLUSIONS: The results of this experimentation confirm the positive effect of the blended learning approach on the acquisition of declarative and procedural knowledge as well as the time management allocated to teaching.